Effects of Metal Poisoning on Total Body Protein in Common House Rat (Masrattus rattus) - Sah, Ramjee; Ray, Shivjee; Kumari, Shweta (Asian Journal of Chemistry, 2010)
Many metals are required for normal physiological functions of human in very low concentrations. However, altered physiological functions result when one or more of these reach sufficiently high concentrations in body cells. In the present investigation the effect of three metal compounds, viz., copper sulphate, cobalt nitrate and Mohr's salt on the total body protein of a terrestrial mammal Masrattus rattus has been studied. It was observed that both the male and the female mice showed decline in the total body protein concentration on the treatment with all these three metal compounds. The decline became increasingly significant with the increase in the concentrations, being most dramatic in the case of copper sulphate. It is assumed that metal ions in high concentrations act as inhibitors to different enzyme systems responsible for protein synthesis.